Hubungan Peran Orang Tua Dengan Perilaku Jajan Tidak Aman Pada Anak Usia Sekolah Dasar Di RW 006 Parigi Lama Pondok Aren Tangerang Selatan - Pasaribu, Sondang Deri Maulina; Komalasari, Oom; Suheti, Suheti; Amelia Putri, Ristina (STIKes IMC Bintaro, 2023)
Introduction: Snacks are one of the foods favored by children. Children and snacks are two things that cannot be separated. One of the factors of this snack habit can worsen the nutritional state of children. Because children are often wrong and do not really understand in choosing snacks, especially if they are not guided by their parents. The role of parents is very important in the process of forming behavior in their children.The purpose of the study: to determine the